Institutional Shutter: Depardon and the Basaglias - Nichols, Maia (Italian Canadiana)

(untitled) (Iter Press, 2024)
This essay discusses Italy’s famous deinstitutionalization movement in the 1970s through the material culture of photography. I focus on film and photographs that provide stunning evidence of the aftermath of the closure of psychiatric hospitals in Italy. The “tearing down” of asylum walls that occurred within reform movements of the 1970s, famously led by Franco and Franca Basaglia, is analyzed by mobilizing photographs in and of Italian hospitals taken by the French photographer Raymond Depardon, whose photographs prove the failure of reform through clothes, games, and objects of restraint. Depardon’s practice offers an opportunity for understanding the habitus that drove the institutional shutter in Trieste, Collegno, and Venice.